Differential responding patterns of the nirK-type and nirS-type denitrifying bacterial communities to an Ulva prolifera green tide in coastal Qingdao areas - Guihua Zhao; Hui He; Ming Yue; Ming Yue; Ming Yue; Hualong Wang; Hongbing Shao; Min Wang; Min Wang; Min Wang (Frontiers in Marine Science, 2022)
Coastal eutrophication may be a vital inducement of green tide. Denitrification is an important nitrogen removal pathway that involves a series of enzymatic reactions. The rate-limiting step in the conversion of nitrite to nitric oxide is encoded by two functionally equivalent but structurally distinct genes, copper-containing nitrite reductase gene (nirK) and cytochrome cd1-containing nitrite reductase gene (nirS). Here, we used Illumina Miseq sequencing approach to examine the variations in denitrifying bacterial community characteristics and interactions during an Ulva prolifera green tide in coastal Qingdao areas. Our findings suggested that the variations in the denitrifying bacterial community structure during the green tide were closely related to the changes of chlorophyll a content, salinity and dissolved oxygen content. The nirK-type denitrifying bacteria were more sensitive to green tide than the nirS-type denitrifying bacteria. Additionally, the nirK-type denitrifying bacterial interactions were more stable and complex during the outbreak phase, while the nirS-type denitrifying bacterial interactions were more stable and complex during the decline phase. All of these characters demonstrated that the nirK-type and nirS-type denitrifying bacteria respond differently to the green tide, implying that they may occupy different niches during the green tide in coastal Qingdao areas.